An Enhanced Path Loss Model for Maritime Communication Channels - Chongquan Wang; Shengming Jiang (IEEE Access)
This study proposes a new ocean propagation loss model, the curved ground loss (CGL) model, to improve the existing models by considering the effects of sea surface roughness, earth curvature, and sea wave height on signal fading at the reflection point. The CGL model integrates a variety of loss factors, including air absorption loss, which has a significant impact on high-frequency and long-distance communications, reflection loss (including diffuse reflection effect and shadow fading), and diffraction loss caused by earth curvature. By comparing with measurement data, the accuracy of the CGL model is verified, achieving an RMSE of approximately 4–5 dB, with the best agreement with the measurement data for four cases: high frequencies, low antennas, the reflection effect and the distance exceeding 60% of the radius of the first Fresnel Zone ( $D_{06}$ ).